Dopamine D2/D3 receptor abnormalities after traumatic brain injury and their relationship to post-traumatic depression. - Jolly, AE; Raymont, V; Cole, JH; Whittington, A; Scott, G; De Simoni, S; Searle, G; Gunn, RN; Sharp, DJ (Elsevier, 2019)
Objective:To investigate dopamine D2/D3 receptor availability following traumatic brain injury (TBI) and theirrelationship to the presence of DSM-IV Major Depressive Disorder (MDD) and patterns of axonal injury.Methods:Twelve moderate-severe TBI patients and 26 controls were imaged using [11C]PHNO positron emissiontomography (PET) and structural magnetic resonance imaging (MRI). TBI patients and a second group of 32controls also underwent diffusion tensor imaging (DTI) and neuropsychological assessment. Patients included sixwith post-injury MDD (TBI-MDD) and six without (TBI-NON). Non-displaceable binding potential (BPND)[11C]PHNO values were used to index D2/D3 receptor availability, and were calculated using a reference regionprocedure. Differences in BPNDwere examined using voxelwise and region-of-interest analyses. White mattermicrostructure integrity, quantified by fractional anisotropy (FA), was assessed and correlated with BPND.Results:Lower [11C]PHNO BPNDwas found in the caudate across all TBI patients when compared to controls.Lower [11C]PHNO BPNDwas observed in the caudate of TBI-MDD patients and increased [11C]PHNO BPNDin theAmygdala of TBI-NON patients compared to controls. There were no significant differences in [11C]PHNO BPNDbetween TBI-MDD and TBI-NON patients. Furthermore, DTI provided evidence of axonal injury following TBI.The uncinate fasciculus and cingulum had abnormally low FA, with the uncinate particularly affected in TBI-MDD patients. Caudate [11C]PHNO BPNDcorrelated with FA within the nigro-caudate tract.Conclusions:[11C]PHNO BPNDis abnormal following TBI, which indicates post-traumatic changes in D2/D3receptors. Patterns of [11C]PHNO BPNDseen in patients with and without MDD suggest that further researchwould be beneficial to determine whether the use of dopaminergic treatment might be effective in the treatmentof post-traumatic depression.